Whither syndemics?: Trends in syndemics research, a review 2015–2019. Issue 7 (2nd July 2020) - Singer, Merrill; Bulled, Nicola; Ostrach, Bayla
ABSTRACT: As originally conceived, syndemics refers to complex epidemics involving two types of adverse interaction – the clustering and interactions of two or more diseases or health conditions (the biological–biological interface) and social environmental factors (the biological–social interface). The theory has been widely applied in the fields of medicine, public health and anthropology, but how the concept is conceptualised and investigated in new syndemics literature remains unclear. This paper offers a scoping review of recent syndemics literature aiming to address the question: Where have scholars taken the syndemics concept? Five bibliographic databases were searched for titles containing 'syndemic[s]' revealing 334 records. A total of 143 journal articles, 23 book chapters, 21 commentaries, 2 books and 5 dissertations were assessed. Citations were classified into five categories: syndemics ( n  = 22), potential syndemics ( n  = 34), socially determined heightened burden of disease ( n  = 29), harmful disease cluster ( n  = 32) and additive adverse conditions ( n  = 71). The limited number of citations meeting the definition of a syndemic arrangement highlights the challenges related to describing and empirically supporting the biological–biological and biological–social relationships. Nevertheless, there is value in retaining the original, holistic, biosocial meaning of syndemics to identify and detail the casual pathways and mechanisms of interactions.